Root Morphology and Growth Response of Oil Palm (Elaeis guineensis Jacq) Hybrid to Al Toxicity at Nursery - Tri Utami; Eka Tarwaca Susila Putra; Tohari Tohari (Jurnal Ilmu Pertanian, 2019)
The purpose of this study was to determine the response of eight oil palm hybrids through root morphological changes and growth to aluminum (Al) toxicity. The research was conducted in Sleman, Yogyakarta in June 2014 - June 2015. The study was prepared in a Factorial Randomized Block Design, with three replications as block. The first factor was was addition of aluminum in two rates (0 ppm and 300 ppm). The second factor eight oil palm hybrids (Yangambi, Avros, Langkat, PPKS 239, Simalungun, PPKS 718, PPKS 540 and Dumpy). The research was conducted at nursery stage. Observed variables include total root length, total root area, root volume, root diameter, aluminum uptake in root, fractal dimension, as well as  fresh and dry root and shoot weight. The data obtained were analyzed by variant (ANOVA) at 5% level, followed by Duncan Multiple Range Test (DMRT) to find out if there was any real difference between the treatments. Aluminum at 300 ppm can change  the morphological character of root, inhibiting root growth and biomass. All the hybrids give  the same respon  on root morphological and growth variables.